Directed assembly of nanoparticles to isolated diatom valves using the non-wetting characteristics after pyrolysis - Jantschke, Anne; Fischer, C.; Hensel, Rene; Braun, H. -G.; Brunner, Eike (Nanoscale, 2014)
A novel strategy for a directed nanoparticle coupling to isolated Stephanopyxis turris valves is presented. After pyrolysis, the valves exhibit incomplete wetting due to their characteristic T-shaped profiles as a prerequisite for a regioselective coupling reaction. A micromanipulation system allows for precise handling and their immobilization onto an adhesive substrate and manipulation into arrays.
CRIS-Team Scopus Importer:2023-03-20